The Use of β-Blockers and the Risk of Undergoing a Knee Arthroplasty. A Nested Case-Control Study. - Tamimi-Mariño, Iskandar Ahmad; García Meléndez, Gaspar; Vieitez-Riestra, Ignacio; Palacios-Penedo, Sergio; Moriel-Garceso, Diego; Sanchez, Alejandro; Tamimi, Faleh; Guerado-Parra, Enrique; Dawid-Milner, Marc Stefan; García-de-Quevedo-Puerta, David; González-Quevedo, David (Wolters Kluwer Health, 2024)
Background: The objective of this study was to analyze the likelihood of total knee arthroplasty (TKA) among patients with OA who were being treated with β-blockers. Methods: A nested case-control study was conducted with use of clinical records from our institutional database. We included patients who attended our outpatient clinic with a history of new-onset knee pain between 2010 and 2019. The case group included individuals who had undergone primary TKA between 2018 and 2019, whereas the control group included subjects who had not undergone TKA. Results: A total of 600 patients were included (300 in the case group and 300 in the control group). Compared with non-users, any use of β-blockers during the follow-up period was associated with a reduction in the likelihood of undergoing TKA (adjusted odds ratio [OR], 0.51; 95% confidence interval [CI], 0.34-0.77). The adjusted ORs for the use of selective β1-blockers and nonselective β1-blockers were 0.69 (95% CI, 0.36 to 1.31) and 0.42 (95% CI, 0.24 to 0.70), respectively. The adjusted ORs for any recent use, PDC of <0.25, PDC of ≥0.25 to <0.75, and PDC of ≥0.75 were 0.65 (95% CI, 0.51 to 0.99), 0.62 (95% CI, 0.21 to 1.85), 0.32 (95% CI, 0.09 to 1.22), and 0.55 (95% CI, 0.34 to 0.88), respectively. Regarding the cumulative effect of β-blockers, the adjusted ORs for the use for <1 year, ≥1 to <5 years, and ≥5 years were 0.41 (95% CI, 0.20 to 0.85), 0.52 (95% CI, 0.21 to 1.33), and 0.36 (95% CI, 0.22 to 0.60), respectively. Conclusions: The use of nonselective β-blockers was associated with a lower likelihood of undergoing TKA. Patients treated for prolonged periods were at a lower likelihood for undergoing TKA.
https://journals.lww.com/jbjsjournal/Pages/Rights-and-Permissions.aspx If you are an author of the article, and JBJS is clearly identified as the copyright holder and the use is entirely non-commercial, you may: - a PDF of the article on a personal or institutional website, or place it in the institutional repository of your academic institution -make a photocopy for personal use -copy the article for the use of your own patients -use your article in an academic dissertation required to obtain an academic degree
Keywords: Rodillas; Operaciones quirúrgicas; Cirugía - Complicaciones y secuelas; Beta-bloqueantes; Beta blockers; β-blockers